2017
DOI: 10.1038/srep41046
|View full text |Cite
|
Sign up to set email alerts
|

Beta-agonist stimulation ameliorates the phenotype of spinal and bulbar muscular atrophy mice and patient-derived myotubes

Abstract: Spinal and bulbar muscular atrophy (SBMA) is a neuromuscular disease characterized by the loss of lower motor neurons. SBMA is caused by expansions of a polyglutamine tract in the gene coding for androgen receptor (AR). Expression of polyglutamine-expanded AR causes damage to motor neurons and skeletal muscle cells. Here we investigated the effect of β-agonist stimulation in SBMA myotube cells derived from mice and patients, and in knock-in mice. We show that treatment of myotubes expressing polyglutamine-expa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 64 publications
1
26
1
Order By: Relevance
“…However, motor impairment has not been observed in AR knockout mice (Yeh et al, 2002) or in severe testicular feminisation patients lacking AR function (Batista et al, 2018). Interestingly, recent reports have shown that muscle may play a more prominent part in disease than previously thought and indeed may be a key site of AR toxicity and the development of pathology in SBMA (Cortes et al, 2014a;Lieberman et al, 2014;Milioto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, motor impairment has not been observed in AR knockout mice (Yeh et al, 2002) or in severe testicular feminisation patients lacking AR function (Batista et al, 2018). Interestingly, recent reports have shown that muscle may play a more prominent part in disease than previously thought and indeed may be a key site of AR toxicity and the development of pathology in SBMA (Cortes et al, 2014a;Lieberman et al, 2014;Milioto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacologic intervention to either silence polyQ-expanded AR expression with antisense oligonucleotides (ASOs) in peripheral tissues, specially skeletal muscle (34), or to promote its degradation and stimulate muscle hypertrophy with the insulin-like growth factor 1 and the beta-agonist clenbuterol (35,36) ameliorated disease manifestations, including metabolic defects in muscle (14). These observations further support the idea that not only the MN, but also the skeletal muscle is central to disease and represents a key target-tissue for therapy development.…”
Section: Introductionmentioning
confidence: 99%
“…Gianni Soraru' discussed findings which suggest that beta2-agonist stimulation of muscle may represent a therapeutic avenue for SBMA and describe plans to undertake a clinical trial of clenbuterol in SBMA patients. Treatment of SBMA knock-in mice with clenbuterol started at disease onset ameliorated motor function and extended survival [68] . Moreover, beta2-agonists have been found to be effective in improving motor function without relevant adverse events in a small cohort of SBMA patients [69] .…”
Section: Clinical Trials For Sbmamentioning
confidence: 93%
“…Importantly, genetic and pharmacologic silencing of polyQ-expanded AR expression in skeletal muscle prevented disease manifestations in mouse [5,6] . Moreover, genetic and pharmacologic approaches to stimulate muscle anabolic pathways and inhibit catabolic pathways, and at the same time reduce polyQ-expanded AR toxicity ameliorated disease manifestations in mouse [6,14,24] .…”
Section: Disease Mechanisms: Peripheral Polyq-expanded Ar Mechanisms mentioning
confidence: 99%